The Historical Implications of the Keraton Yogyakarta on the Conception of Place in the Jeron Beteng Area, Yogyakarta - Emmelia Tricia Herliana (RUANG: Jurnal Lingkungan Binaan (SPACE: Journal of the Built Environment), 2024)
The Sultanate of Yogyakarta has been a distinct part of the characters associated with Yogyakarta City. The Jeron Beteng area, which is administratively located in the District of Kraton, was in the past the center of this Sultanate. It becomes part of historical journeys that construct the identity of Yogyakarta city as a place. Since its confirmed status as a heritage zone, the Jeron Beteng continuously attracts increasing tourists. It becomes subject to continuous land use, traffic, migration, and land ownership changes. As a result, the identity of the place has been transformed unclearly. This study views that, understanding the conception of a Jeron Beteng area as a place is essential to preserve its identity. It explores the dynamics of this conception based on cultural significances derived from historical events between 1755 and the present time. The research question is "How does the existence of the Keraton Yogyakarta affect the concept of place of the Jeron Beteng Area?" This study uses a historical-comparative method supported by secondary data. Data analysis is based on political, economic, social, and cultural influences on each phase of the Sultan's reign. Study results reveal that political, economic, social, and cultural conditions in each era of the Sultan's reign affect the dynamics of place conception of the Jeron Beteng area.Keywords: the conception of place; Jeron Beteng area; historical events; a cultural value AbstrakKasultanan Yogyakarta telah menjadi bagian khas dari karakter yang diasosiasikan dengan Kota Yogyakarta. Kawasan Jeron Beteng yang secara administatif terletak di Kecamatan Kraton dahulu merupakan pusat kesultanan ini. Kawasan ini menjadi bagian perjalanan sejarah yang membangun identitas Kota Yogyakarta sebagai sebuah tempat. Sejak penunjukannya sebagai cagar budaya, Kawasan Jeron Beteng secara berkelanjutan mengalami peningkatan jumlah kunjungan wisatawan. Kawasan ini telah mengalami perubahan yang terus-menerus dalam alih fungsi lahan, lalu lintas, migrasi, dan kepemilikan lahan. Identitas tempat telah ditransformasi secara tidak jelas. Studi ini memandang jika memahami konsepsi Kawasan Jeron Beteng sebagai sebuah tempat dalam rangka melestarikan identitasnya merupakan hal yang esensial. Penelitian ini bertujuan untuk menggali dinamika dari konsepsi ini berdasarkan tata nilai budaya yang diderivasi dari beragam peristiwa sejarah yang terjadi dari tahun 1755 sampai sekarang. Pertanyaan penelitian yang digali adalah “Bagaimana keberadaan Keraton Yogyakarta mempengaruhi konsep tempat dari Kawasan Jeron Beteng?” Penelitian ini menggunakan metode historis-komparatif didukung oleh data sekunder. Analisis data didasarkan pada pengaruh aspek politik, ekonomi, sosial, dan budaya dari setiap era pemerintahan Sultan. Hasil penelitian menunjukkan bahwa kondisi politik, ekonomi, sosial dan budaya pada setiap era pemerintahan Sultan mempengaruhi dinamika konsep tempat di kawasan Jeron Beteng.Kata kunci: konsepsi tempat; Kawasan Jeron Beteng; peristiwa-peristiwa sejarah; nilai budaya